Balanced Scorecard: Management control analysis in a private dental healthcare clinic - Caldeirão, A.; Conceição, A. (Proceedings of the International Workshop on Accounting and Taxation (IWAT2024), 2024)
Purpose: This study aims to analyse the implementation of the Balanced Scorecard (BSC) as a management control tool in a dental clinic. Therefore, a proposal of this model is presented, including the development of a strategic map specifically tailored for a small private healthcare organization. Methodology: A qualitative methodology was adopted, following the principles outlined by Yin (2018), through the implementation of an interventionist case study (Baard and Dumay, 2020). Results: The case highlighted the existence of a culture that tends to be neobureaucratic (Dey et al., 2006), revealing flexibility, however top-down, with the final decision-making power centralized in a single person responsible. Research limitations: The BSC implementation process can be complex. The cycle of planning, implementation, and performance monitoring is an ongoing process that was not fully addressed due to time constraints. The research relied predominantly on data acquired from interviews; however, the combination of qualitative methods and literature review strengthens the understanding of the study at hand. Originality: This study contributes to the literature on the BSC, providing pragmatic insights tailored to the unique needs of small-scale organizations in the private healthcare sector.